Types of evolution in human retroviruses: Systematic review (Research, Society and Development, 2024)
Viral evolution, especially in retroviruses, is a complex and dynamic process that can be influenced by interactions with the host and different selective pressures. This evolution can be classified as neutral, in which most genetic changes are caused by the effect of genetic drift, or positive, where diversity would be maintained by a balance between the mutation rate and its eventual maintenance due to the effects of natural selection. For this study, we conducted a systematic review with the aim of classifying retroviruses according to the evolutionary theory they fit. In the 75 articles analyzed, it was possible to observe a predominance of positive selection (76%), especially in human immunodeficiency viruses (HIV), corroborated by the prevalence of non-synonymous mutations identified, where "beneficial" mutations are selected, possibly as a response to immune system pressures and treatments. When comparing the evolution of HIV with the human endogenous retrovirus (HERV), different patterns were observed, HERV viruses tend to purifying selection, maintaining pre-existing characteristics and, in co-infection scenarios with HIV, HERVs tend to neutral selection, with accumulation of synonymous mutations. The study and understanding of evolutionary processes and the factors that influence them are of paramount importance, since the emergence of resistant variants is currently the biggest obstacle in the development of an effective treatment for retroviral infections.